Trust and Accountability: Legal Implications of Train Delays: Kepercayaan dan Akuntabilitas: Implikasi Hukum dari Keterlambatan Kereta Api - Churniawan, Erifendi (Universitas Muhammadiyah Sidoarjo, 2023)
This normative legal research with statutory and conceptual approaches aims to analyze the implications of train delays according to schedule in a progressive legal perspective and to construct ethical and legal responsibility for such delays. The results reveal that train delays not only harm passengers but also decrease public trust in rail services. In a progressive legal perspective, trust is the fundamental element for law to serve human interests. To address this issue, a minister of transportation regulation should be established to hold train service managers accountable for delays and provide ethical and legal obligations to passengers. By learning from the accountability of aircraft delays, such regulations can be adapted to rail transportation. Highlights: Train delays have negative consequences for passengers and public trust in rail services. Trust is a fundamental element for law to serve human interests. A minister of transportation regulation should be established to hold train service managers accountable for delays and provide ethical and legal obligations to passengers.